Konglomerasi, Merger, dan Skala Ekonomi Tahap Pertumbuhan Industri - Rifdatul Hanifah; Muhammad Yasin (Jurnal Riset Ekonomi dan Akuntansi, 2024)
In facing global market dynamics, companies tend to look for conglomeration or merger strategies to achieve greater economies of scale and increase their competitiveness. Conglomeration, mergers, and economies of scale are concepts related to industrial growth. Conglomeration refers to the merger of several companies operating in the same or related industries. A merger, on the other hand, is the merging of two different companies into one new entity. Economies of scale, in the growth stage of an industry, refer to the cost savings that occur when a company increases production by enlarging a factory.